Аnalysis of automated control systems implementation on the railway transport (Transport systems and technologies, 2019)
The article analyzes the introduction of automated control systems on the rail transport. The current state and prospects of the innovative information technologies development in the field of railway transportation have been investigated. The advantages and disadvantages of Automated Workplaces functioning (hereinafter - AWP) have been considered. The advantages in implementing electronic document flow have been justified.The present stage of rail transport development is characterized by the transition to universal informatization, the introduction of computerization and information technology in all areas.In this regard, the solution to the problem of using modern, promising methods and means of information processing in practical activities is of paramount importance.Qualitatively new opportunities for the information provision of the transportation process management with the solution of the problems on automation of information transmission and implementation of corporate information systems have appeared.Today, railway transport is greatly competitive with the other forms of transport modes; therefore, apart from modernizing the technical equipment of the transportation process, it is important to improve customer service and information support.The introduction of the Automation Workplace system (AWS), an electronic documentt flow system certainly gives an effect and contributes to the safety of freight transportation. This will make it possible to attract customers to the transportation process, to select an acceptable delivery option, and make it possible to make an optimal selection of wagons for a certain cargo rates.
Keywords: railway transport, automated workplace, electronic document flow, automated system, information technology, microprocessor system